PENGEMBANGAN APLIKASI MANAJEMEN LABORATORIUM PENDIDIKAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERIMAKASSAR BERBASIS SCRAPING DATA WEB TO ANDROID - Ilhamka Ilhamka; Purnamawati; Yasser Abdul Djawat (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This type of research is development research (Research and Development) which aims to find out the results of developing a laboratory management application based on web data streaming to Android and find out user responses to the implementation of the design results. The type of research used is development research or Research and Development (R&D). The number of respondents was 20 people using individual trials, small group trials and field trials. The research results show that PKK Laboratory Management can help laboratory management activities of the PKK FT UNM Department. With this web-based laboratory management information system, users can process information more easily and quickly. The results of the Functionality Testing carried out by the system expert were declared suitable for use, where the system expert assessed two main indicators, namely the login menu and administrator menu, where the results obtained were an average of 4.36 with 87.12% being in the Strongly Agree criteria. Usability testing on laboratory management applications based on web to Android data streaming with user response results with a mean of 3.77 with a percentage of 94.15% in the Very Good criteria.